KERAGAMAN MORFOLOGI UBI JALAR (Ipomoea batatas (L.) Lam.) ASAL KABUPATEN MUNA - Warhamni, Warhamni; Boer, Dirvamena; Muzuni, Muzuni (Jurnal Agroteknos, 2013)
This research aimed to study the morphological diversity of sweet potatoes in Muna regency. The morphological observation was performed to analyze both quantitative and qualitative characteristics of sweet potatoes. The morphological data were then analysed. The qualitative characteristics were presented in binary data. The quantitative data were firstly standardized. Then, the genealogical relationship of qualitative characteristics was analyzed using the Match Matching of genetic distance, and the genealogical relationship of quantitative characteristics was analyzed using Euclidian genetic distance. The genealogical relationship was calculated through genetic distance, which informs the genetic differences between populations. The results of the analysis showed that sweet potatoes in Muna beared similarities, although their dissimilarity coefficient value was small. Keywords: Sweet potatoes, Morphological, Genealogical Relationship